Analysis of Factors Inhibiting the Implementation of Patient Medical Record Retention and Destruction Activities at Waluyo Jati Hospital - Afifah, Lilik; Fitriyani, Endang; Pertiwi, Yunita Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Retention and destruction of medical record documents is a management aspect in health archives to reduce files that have been stored on the filling rack for a long time. This study aims to analyze the factors that hinder the implementation of retention and destruction of medical record documents at RSUD Waluyo Jati. Qualitative descriptive method was used to analyze these factors with data collection using the 5M approach. The results showed that the main obstacles were the lack of D3 Medical Record graduates and the lack of training related to document retention and destruction. RSUD Waluyo Jati does not have an SPO (Standard Operating Procedure) related to retention and planning document retention and destruction schedules and still uses the old ICU room to store inactive documents. Other problems include the lack of shredding and file transfer equipment, and the absence of a dedicated budget for these activities. The conclusion of this study emphasizes the importance of implementing retention and destruction of medical record documents in managing efficient archives. As a solution, efforts such as increased education and training for staff, the development of comprehensive SOPs, planning document retention schedules, improving infrastructure, collaboration with third parties, and proper budget allocation are needed to ensure the effectiveness of the medical record retention and destruction process.